ANAK SEBAGAI TENTARA DALAM KONFLIK BERSENJATA MENURUT PERSPEKTIF HUKUM HUMANITER INTERNASIONAL DAN KONVENSI HAK ANAK 1989 - Lay Riwu, Agustiyono Elfondag; Kase, Dhesy A; Bunga, Gerald Aldytia (Petitum Law Journal, 2023)
War and conflict have become an inseparable part of human history. One of the victims of war is children who are actually the forerunners of the continuation of life and the future of mankind .It is on this basis that various provisions in international law emerged to recognize children's rights and protect children from armed conflicts, including the 1989 Convention on the Rights of the Child. Nevertheless, exploitation of children in armed conflicts still occurs in various parts of the world. This study aims to re-examine the mechanism of child protection in the 1989 Convention on the Rights of the Child and related provisions and to look at its implementation and weaknesses in order to find solutions to increase the effectiveness of implementing these provisions. The main source of this research is the 1989 Convention on the Rights of the Child and its additional Protocols, accompanied by UN reports on various gross violations of children's rights in various countries.Based on the results of the research, it was found that in various countries in the world the number of uses of children in armed conflicts is still very concerning, Thus, it was concluded that a better approach and more concrete efforts from various parties are needed to reach a resolution and stop conflicts that continue to victimize children.